2020
DOI: 10.1080/02602938.2020.1845607
|View full text |Cite
|
Sign up to set email alerts
|

Assessment policies and academic progress: differences in performance and selection for progress

Abstract: Despite the benefits swift academic progress holds for many stakeholders, there is scarce literature on how academic progress may be improved by changes to assessment policies. Therefore, we investigated academic progress of first-year students after an alteration of characteristics of the assessment policies in three large course programmes: business administration (n ¼ 2048) changed the stakes; medicine (n ¼ 1630) changed the stakes and performance standard; psychology (n ¼ 1076) changed the stakes, performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Given this perspective, the absence of resit effects in the PAL task could therefore be taken to argue against the presence of resit effects in settings requiring actual learning. On the other hand, concerns about negative effects of a resit prospect in educational settings requiring actual learning have been expressed in the literature ( Al-Bayatti & Jones, 2003 ; Burr et al, 2018 ; Centre for Education Research and Policy, 2012b , 2012a ; Kickert et al, 2020 ; McManus, 1992 ; Non & Tempelaar, 2016 ; Pell et al, 2009 ; Ricketts, 2010 ; Scott, 2012 ; Yocarini et al, 2018 ), and have indeed been found in a field study by Grabe ( 1994 ; for similar findings, see Centre for Education Research and Policy, 2012b ). Therefore, the notion of resit effects in settings requiring actual study time to be allocated to learning materials should perhaps not be dismissed just yet.…”
Section: Discussion Experiments 1 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this perspective, the absence of resit effects in the PAL task could therefore be taken to argue against the presence of resit effects in settings requiring actual learning. On the other hand, concerns about negative effects of a resit prospect in educational settings requiring actual learning have been expressed in the literature ( Al-Bayatti & Jones, 2003 ; Burr et al, 2018 ; Centre for Education Research and Policy, 2012b , 2012a ; Kickert et al, 2020 ; McManus, 1992 ; Non & Tempelaar, 2016 ; Pell et al, 2009 ; Ricketts, 2010 ; Scott, 2012 ; Yocarini et al, 2018 ), and have indeed been found in a field study by Grabe ( 1994 ; for similar findings, see Centre for Education Research and Policy, 2012b ). Therefore, the notion of resit effects in settings requiring actual study time to be allocated to learning materials should perhaps not be dismissed just yet.…”
Section: Discussion Experiments 1 Andmentioning
confidence: 99%
“…In line with this reasoning, research has shown that students’ academic performance does indeed seem to be sensitive to differences in the specific rules making up assessment policies, possibly through motivational and self-regulatory factors ( Elikai & Schuhmann, 2010 ; Johnson & Beck, 1988 ; Kickert et al, 2018 , 2019 ). Further research has also shown that academic performance ( Kickert et al, 2020 ) and study delays ( Schmidt et al, 2021 ) might be affected by changes in resit policies specifically. Moreover, in another study it was reported that students, at least those who are impatient, tend to not exert sufficient effort to pass through the first exam and instead shift their study efforts to the resit exam ( Non & Tempelaar, 2016 ).…”
Section: Evidence For the Resit Effectmentioning
confidence: 99%
“…Given 2012b, 2012aKickert et al, 2020;McManus, 1992;Non & Tempelaar, 2016;Pell et al, 2009;Ricketts, 2010;Scott, 2012;Yocarini et al, 2018), and have indeed been found in a field study by Grabe (1994; for similar findings, see Centre for Education Research and Policy, 2012b), as well as in more abstract studies using the study-time investment task . Therefore, the notion of resit effects in settings requiring actual study time to be allocated to learning materials should perhaps not be dismissed just yet.…”
Section: Implications For the Resit Effectsupporting
confidence: 53%
“…In line with this reasoning, research has shown that students' academic performance does indeed seem to be sensitive to differences in the specific rules making up assessment policies, possibly through motivational and self-regulatory factors (Elikai & Schuhmann, 2010;Johnson & Beck, 1988;Kickert et al, 2018Kickert et al, , 2019. Further research has also shown that academic performance (Kickert et al, 2020) and study delays (Schmidt et al, 2021) might be affected by changes in resit policies specifically.…”
Section: Evidence For the Resit Effectmentioning
confidence: 88%
“…This is also a possible explanation for the fact that a previous study focusing on PAP did find more promising results with respect to predicting early academic performance, since that study did not control for pu-GPA [ 20 ]. Another possible explanation for this difference in findings is that contrary to the programs in the previous study, the medical program used selection, which can lead to higher overall academic performance [ 50 ], and potentially better prepared students. Nevertheless, as male students and students with sociodemographic minority backgrounds perform poorer in medical school [ 36 , 37 ], the lack of interaction effects between participation and these variables suggests that the preparatory activities in their current form do not contribute to reducing this performance gap.…”
Section: Discussionmentioning
confidence: 77%